2021
DOI: 10.1111/jocn.15780
|View full text |Cite
|
Sign up to set email alerts
|

Examining the utility of the Violence Prevention Climate scale: In a metropolitan Australian general hospital

Abstract: Aim and objectives To evaluate and examine the utility of the Violence Prevention Climate scale by generalist healthcare professionals. Background Workplace violence in general hospital settings remains a challenge for healthcare organisations. High rates of violence are still being reported towards healthcare workers, despite organisational violence prevention strategies being implemented. There is a major challenge to healthcare organisation in the measurement of the effectiveness of these interventions, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…While drugs and alcohol are often blamed for ED violence in the literature (Ramacciati et al, 2017) these do not always appear to be the major influencing factor (Al‐Maskari et al, 2020; Ramacciati, Ceccagnoli, Addey, & Rasero, 2018; Zoleo et al, 2020). Indeed, a recent examination of risk revealed that those deemed at greater risk of violence were patients with mental health disorders (Brunero et al, 2021). For example, Connor et al (2020) found that most (57%) of the violent episodes reported in the ED were mental health related, whereas very few cases (2%) were related to drugs or alcohol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…While drugs and alcohol are often blamed for ED violence in the literature (Ramacciati et al, 2017) these do not always appear to be the major influencing factor (Al‐Maskari et al, 2020; Ramacciati, Ceccagnoli, Addey, & Rasero, 2018; Zoleo et al, 2020). Indeed, a recent examination of risk revealed that those deemed at greater risk of violence were patients with mental health disorders (Brunero et al, 2021). For example, Connor et al (2020) found that most (57%) of the violent episodes reported in the ED were mental health related, whereas very few cases (2%) were related to drugs or alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…While drugs and alcohol are often blamed for ED violence in the literature (Ramacciati et al, 2017) these do not always appear to be the major influencing factor (Al-Maskari et al, 2020;Zoleo et al, 2020). Indeed, a recent examination of risk revealed that those deemed at greater risk of violence were patients with mental health disorders (Brunero et al, 2021).…”
Section: Reasons For Violence In the Emergency Departmentmentioning
confidence: 99%
See 2 more Smart Citations